Tenure (in)security and agricultural investment of smallholder farmers in Mozambique - Ghebru, Hosaena (International Food Policy Research Institute, 2013)
Using the case of past and ongoing land tenure reforms in Mozambique, this paper aims at assessing the determinants of tenure security for households and the implications of such tenure security on their observed behavior in undertaking long-term land-related investments. An attempt is made to distinguish the source of risk of tenure insecurity as: (i) effective risk (mainly dependent on past experiences of households); and (ii) potential risk (i.e., long-term perception of tenure security).